Small Interfering RNA Delivery Into Primary Human Natural Killer Cells for Functional Gene Analyses. Issue 11 (28th November 2022) - Momayyezi, Pouria; Malmberg, Karl‐Johan; Hammer, Quirin
Abstract: Studying gene functions in human natural killer (NK) cells is key for advancing the understanding of NK cell biology and holds promise to pave the way for improving NK cell therapies against cancer. However, NK cells are challenging to manipulate, and investigation of gene functions in NK cells is hampered by variable delivery efficiencies and impaired viability upon electroporation, lipofection, or viral transduction. Here, we report a simple workflow for delivery of commercially available small interfering RNA molecules into primary human NK cells to enable functional gene analyses. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Enrichment of natural killer cells from human peripheral blood mononuclear cells Basic Protocol 2 : Preparation of small interfering RNA Basic Protocol 3 : Delivery of small interfering RNA into natural killer cells Support Protocol 1 : Isolation of human peripheral blood mononuclear cells from buffy coats Support Protocol 2 : Thawing and recovery of cryopreserved peripheral blood mononuclear cells Support Protocol 3 : Evaluation of natural killer cell purity following magnetic enrichment Support Protocol 4 : Exemplary assessment of knockdown efficiency